Turn-Taking Strategy on Spiderman on No Way Home Cast’s Interviews: Discourse Analysis - Kistina Aulia; Ervina CM Simatupang (Ethical Lingua: Journal of Language Teaching and Literature, 2022)
The aims of this research are to find the turn-taking strategy used and the factor of strategy found in turn-taking strategy. The data was taken from Spiderman: No Way Home Cast’s Interviews in CinemaBlend Youtube Channel. The research method used in this research is a qualitative method and the turn taking theory used here is theory by Anna-Brita Stenström. In collecting the data, several steps are applied in this research; finding the sources for the data, watching the video which is an object for analysis, transcribing the script, analyzing the script, describing the result of the research and making a conclusion of the research. The result of the strategy is classified based on the type of each strategy, starting up (11%), interruption (17%), filled pause and verbal filler (30%), silent pause (13%), lexical repetition (25%), prompting (2%) and appealing (2%). According to the findings, the most common types in this study were filled pause and verbal filler. 'uh' and 'mmm' are the most common expressions associated with filled pauses and verbal fillers. The speaker would typically hesitate for a second before muttering the verbal fillers and resume their sentence.